Design of an interactive digital encyclopedia of Palembang urban culture on a web-based HTML5 platform as an implication for BIPA learning - Mayrita , Hastari; Sahfitri, Vivi; Aprilia, Fitria; A. Abdillah, Leon; Saputra, Haris (Edelweiss Applied Science and Technology, 2024)
The need for BIPA (Indonesian Language for Foreign Speakers) learning facilities, particularly in the form of materials and audio-visual learning media, is critical. This can also serve as an attraction for tourists interested in learning the Indonesian language. An interactive digital encyclopaedia is an application that provides access to knowledge in a digital format. This medium facilitates users in accessing information, following links, watching videos, listening to audio, and participating in quizzes and educational games digitally. The aim of this research is to design an interactive digital encyclopaedia of Palembang urban culture on a web-based HTML5 platform as a communicative learning support medium for Indonesian language learners who are non-native speakers. Qualitative case study approach combined with the 4D development model was employed. The case study helps researchers identify language, culture, and arts that could have implications for BIPA learning. The 4D development model was used to design the interactive digital encyclopaedia application on a web-based HTML5 platform. The design themes include language, art, and culture in Palembang, which are further broken down into several topics based on the BIPA syllabus: Introduction, Geography and Demography of Palembang, Language and Literature, Palembang Culture, Architecture Heritage, Social and Religious, Economy and Daily Activities, Interactive, Glossary, References, and Team. The novelty of this research lies in the design of an interactive digital encyclopedia of Palembang’s urban culture on a web-based HTML5 platform. The content not only describes Palembang’s culture but also aligns with the BIPA program’s policies, syllabus, and learning outcomes.